2020
DOI: 10.1186/s12929-020-00668-5
|View full text |Cite
|
Sign up to set email alerts
|

ZNF322A-mediated protein phosphorylation induces autophagosome formation through modulation of IRS1-AKT glucose uptake and HSP-elicited UPR in lung cancer

Abstract: Background: ZNF322A is an oncogenic transcription factor that belongs to the Cys2His2-type zinc-finger protein family. Accumulating evidence suggests that ZNF322A may contribute to the tumorigenesis of lung cancer, however, the ZNF322A-mediated downstream signaling pathways remain unknown. Methods: To uncover ZNF322A-mediated functional network, we applied phosphopeptide enrichment and isobaric labeling strategies with mass spectrometry-based proteomics using A549 lung cancer cells, and analyzed the differenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 67 publications
(84 reference statements)
1
5
0
Order By: Relevance
“…Many members of zinc finger transcription factor family could be associated with tumor prognosis and patient outcomes, such as ZNF191, ZNF71, and ZNF322 (24,36). In addition, the higher the level of ZNF71 the better the survival of NSCLC patients, which is similar to our results that high levels of ZNF24 expression in NLSCLC patients were significantly associated with longer survival in all stages.…”
Section: Discussionsupporting
confidence: 89%
“…Many members of zinc finger transcription factor family could be associated with tumor prognosis and patient outcomes, such as ZNF191, ZNF71, and ZNF322 (24,36). In addition, the higher the level of ZNF71 the better the survival of NSCLC patients, which is similar to our results that high levels of ZNF24 expression in NLSCLC patients were significantly associated with longer survival in all stages.…”
Section: Discussionsupporting
confidence: 89%
“…Thus, insulin-stimulated glucose uptake in the skeletal muscle depends on GLUT-4 expression at the plasma membrane [ 22 ]. Phosphorylation of IRS-1 and AMPK positively regulates the activation of GLUT-4 [ 23 ]. Therefore, upregulation of GLUT-4 in association with phosphorylation of IRS-1 and AMPK indicated that α-Spinasterol improved glucose uptake by translocating GLUT-4 to the skeletal muscle plasma membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the key regulons, we constructed a multimarker model by the SVM method, which had an AUC equal to 1 to effectively predict HSCR. It has been reported that PIM3 , a proto-oncogene with serine/threonine kinase activity, could regulate cell migration and apoptosis via PI3K–AKT, p38, or Rho GTPase signaling,56–58 and was related to demyelinating disease 59. Inhibitor-κB kinase α, which is encoded by the CHUK gene, was recognized to regulate NF-κB activity60 61 and involved the differentiation of mouse embryonic neuroectoderm.…”
Section: Discussionmentioning
confidence: 99%